Reference-free measurements of the 1s2s2p 2 P1/2,3/2o →1s22s 2S1/2 and 1s2s2p 4P5/2→1s22s 2S1/2 transition energies and widths in lithiumlike sulfur and argon ions - Machado, Jorge (2021)
PEstOE/FIS/UI0303/2011 PTDC/FIS/117606/2010 PTDC/FIS-AQM/31969/2017 UID/FIS/04559/2019 SFRH/BD/52332/2013 Contract No. EMMI HA-216 Hubert Curien PESSOA 38028UD PAUILF 2017-C08 Grant No. 01 3 0002 Grant No. ANR-06-BLAN-0223 Grant No. 70NANB15H051